Food for special needs - Harding, Ben; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2005)
Examines food allergies and intolerances, dietary diseases and disorders. Cultural and religious beliefs that determine diet also considered
Title from title screen
Executive producer, Mark McAuliffe ; sound, Wayne Martin ; graphic, Paul Sutherland
Voice over: Mark Collard
Keywords: Food allergy; Dietaries; Nutrition